Effects of some pesticides on in vitro male gamethophyte performance of Prunus armeniaca (apricot) and Persica vulgaris (peach) plants - Topdemir, Aykut; Gür, Nazmi (My University, 2013)
The aim of this study is to investigate effects of pesticides on in-vitro polen germination and tube length of Primus armeniaca L. and Persica vulgaris plants. Primus armeniaca L. and Persica vulgaris flowers have been exposed 5 different solutions of Carbendazim and Thiodan pesticides which was diluted with distilled waterby half in a row one by one. Brawbaker Kwack medium was used for pollen germination. Apricot pollen germination percentage rate was decreased to % 39.51 and % 77,67 for tube length; % 44,27 Persica vulgaris pollen germination and % 60,94 for tube length with carbendazim pesticide solutions. Also Apricot pollen germination percentage rate was decreased to % 47,62 and % 92,42 for tube length; % 71.41 Persica vulgaris pollen germination and % 60,18 for tube length with thiodan pesticide.
Bildiri - Yayımlanmamış
Keywords: Prunus armeniaca L.; Persica vulgaris; Pesticides; Effects; Male gamethophyte